A grounded theory of the implementation of medical orders by clinical nurses - Monireh Asadi; Fazlollah Ahmadi; Easa Mohammadi; Mojtaba Vaismoradi (BMC, 2024)
Abstract Objective To explore the process of implementing medical orders by clinical nurses, and identify specific areas of concern in the implementation process, and uncover strategies to address these concerns. Background The implementation of medical orders is a crucial responsibility for clinical nurses, as they bear legal accountability for the precise implementation of directives issued by medical practitioners. The accurate implementation of these orders not only shapes the quality and safety of healthcare services but also presents numerous challenges that demand careful consideration. Method This study employed a qualitative design using a grounded theory approach to construct a comprehensive theoretical framework grounded in the insights and experiences of nurses operating within the hospital settings of Iran. The study encompassed 20 participants, comprising 16 clinical nurses, two nurse managers, and two specialist doctors working in hospital settings. The selection process involved purposeful and theoretical sampling methods to ensure diverse perspectives. Data collection unfolded through in-depth, individual, semi-structured interviews, persisting until data saturation was achieved. The analytical framework proposed by Corbin and Strauss (2015) guided the process, leading to the development of a coherent theory encapsulating the essence of the study phenomenon. Findings The primary finding of the study underscores the significance of 'legal threat and job prestige' highlighting diverse repercussions in case of errors in the implementation of medical orders. At the core of the investigation, the central variable and the theory of the study was the 'selective and tasteful implementation of orders to avoid legal and organizational accountability.' This indicated a set of strategies employed by the nurses in the implementation of medical orders, encapsulated through three fundamental concepts: 'accuracy in controlling medical orders,' 'untruth documentation,' and 'concealment of events. The formidable influence of legal threats and job prestige was further compounded by factors such as heavy workloads, the doctor's non-compliance with legal instructions for giving verbal orders, the addition of orders by the doctor without informing nurses, and pressure by nursing managers to complete documentation. The resultant psychological distress experienced by nurses not only jeopardized patient safety but also underscored the intricate interplay between legal implications and professional standing within the healthcare framework. Conclusion Alleviating staff shortages, enhancing the professional rapport between doctors and nurses, offering legal support to nursing staff, implementing measures such as recording departmental phone conversations to deter the non-acceptance of verbal orders, fostering an organizational culture that embraces nurse fallibility and encourages improvement, and upgrading equipment can ameliorate nurses' apprehensions and contribute to the safe implementation of medical orders.